A review of knowledge LTD: Towards a social logic of the derivative - SAITO, Hiro (Institutional Knowledge at Singapore Management University, 2016)
California program for paid family leave.They find that higher-wage employees aremore likely to gain such benefits and to usethem, while low-wage workers are less likelyto have them available or know about themand are less likely to use them, because theprogram does not pay enough or providejob protection.